Compound-complex odontoma: A case report of a rare variant - Nishath Khanum; Mahesh Mysore Shivalingu; Naresh Lingaraju; Srisha Basappa (Wolters Kluwer Medknow Publications, 2014)
The odontoma is a benign tumor containing all the various component tissues of the teeth. It is the most common odontogenic tumor representing 67% of all odontogenic tumors. Odontomas are considered to be developmental anomalies (hamartomas) rather than true neoplasms. Based on the degree of morphodifferentiation or on the basis of their resemblance to normal teeth, they are divided into compound and complex odontomas. The compound odontoma is composed of multiple, small tooth-like structures. The complex odontoma consists of a conglomerate mass of enamel and dentin, which bears no anatomic resemblance to a tooth. They are usually diagnosed on routine radiological examinations in the second decade of life and are often slow growing and non-aggressive in nature. Here, we report a case of rare, unusually large, compound-complex odontoma, located in the left anterior maxilla of a 13-year-old male patient.